PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI PADA UMKM CATHS BEAUTY HOUSE DALAM SEKTOR JASA DI KOTA BATAM - Huang, Chyntia; Flowerensia, Dionna; Feby; Safitri, Yolanda Alya (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
Caths Beauty House is a small-medium enterprise (SME) located in Batam, Riau Islands, Indonesia. This SME has been established since 2017 and has developed by increase in customers every year. Main service that is offered by Caths Beauty House is eyebrow embroidery and eyelash extension. This study aims to analyze how does the demand for this SME growing and fluctuate over the years, analyze how Caths Beauty House manage its overdemand and overcapacity, as well as recommend the SME on managing its demand to reduce demand fluctuations and increase the profitability of SME by reducing opportunity and inventory cost.